(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2008)
A remarkable pupil of the great physicist Werner Heisenberg, the German Hans-Peter Dürr, born 1929, was granted the Alternative Nobel Prize in 1987 for his work in favor of peaceful use of high technology and is also one of the members of the Pugwash group of scientists that received the Nobel Prize for Peace in 1995. His scientific experience as a quantum physicist of the highest rank is the departure point of a philosophical thought with revolutionary consequences. This article tries to present the lines along which this very sophisticated philosophy develops, hinting at connections with modern and ancient thinking. The transformative character of Dürr’s teachings opens the way to further elaborations in almost any field. This article is an invitation to anyone, but especially to peace workers, to join in this demanding but promising and highly enriching task.